DISTRIBUTION OF INHERITANCE AGAINST GIRLS: Analysis Study in Tanjung Mompang Village, Panyabungan Utara District, Mandailing Natal Regency - Nasution, Nindi Aliska (Universitas Islam Indonesia, 2020)
The inheritance is the transition of wealth from one who is edited to his heir realized after the heir passed away. The problems that arise in this study are many people or communities who don't understand the science of Mawaris. In some cases about inheritance in Indonesia, one of which is located in Tanjung Mompang Village, Panyabungan North , South Mandailing Natal, carried out the distribution of inheritance based on traditions that existed and implemented without reference to the provisions of Islamic law. Using a juridical-empirical approach, the paper argued that the division of inheritance in some areas of the population was a majority of Islam but did not prioritize Islamic law in its religious matters, especially those occurring in the village of Tanjung Mompang in Payabungan North , South Mandailing Christmas . There are two focus problems in this paper, 1. How is the implementation of inheritance of property to girls in Tanjung Mompang village? 2. What are the factors that cause the people of Tanjung Mompang Village to implement the distribution of inheritance based on the tradition? The result of this research is the distribution of inheritance that is done in the tradition because of the lack of public awareness about the rule of law in the Division of inheritance and one of the very basic factors that the division of inheritance That is done not legally Islamic which is primarily a public ignorance of the procedure, and consequently many feel unfair, causing a dispute over fellow brothers in the family.